High-temperature-resistant waterproof PET label and preparation process thereof

By coating PET labels with epoxy silicon coating and hydrophobic adhesive to form an antibacterial and waterproof layer, the problems of blurred information and bacterial growth on PET labels in humid environments are solved, and the long-term clarity, readability and safety of the labels are achieved.

CN120564523BActive Publication Date: 2025-10-21HANKAN (GUANGZHOU) NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510883264.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-28
Publication Date
2025-10-21
Estimated Expiration
2045-06-28

AI Technical Summary

Technical Problem

Existing PET labels are prone to blurred information and falling off in humid or oily environments, and there is a risk of cross-contamination due to bacterial or mold growth. Their insufficient waterproof performance affects the long-term readability and safety of the labels.

Method used

By coating the surface of a PET film with an epoxy silica coating containing chitosan-coated titanium dioxide and modified chitosan microspheres, an antibacterial and waterproof layer is formed. This layer is then combined with a hydrophobic adhesive to create a dual-barrier structure that enhances both antibacterial and waterproof properties.

Benefits of technology

It achieves adhesive stability and antibacterial properties for PET labels in humid environments, preventing bacterial invasion, maintaining the clarity of label information, and preventing moisture penetration, thereby improving the durability and security of the labels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005472939180000121
    Figure BDA0005472939180000121
Patent Text Reader

Abstract

The present application relates to the technical field of PET label, and particularly relates to a high-temperature-resistant waterproof PET label and a preparation process thereof. The present application obtains antibacterial modified chitosan microspheres by adding chitosan, nano titanium dioxide, span 80 and cinnamaldehyde; the antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane and a curing agent are mixed to obtain an epoxidized silicon coating. The epoxy resin is heated to be molten, and then hydrophobic silicon dioxide, a curing agent, dioctyl phthalate and acetone are added and uniformly stirred to obtain an adhesive. The epoxidized silicon coating is coated on the surface of a PET film, and then is left to stand and solidify to obtain a waterproof PET film; one side of the waterproof PET film is coated with the adhesive and is combined with a PET release base paper, and the other side of the PET film is coated with ink to obtain a finished product. The finished product prepared by the present application has excellent antibacterial performance and waterproof performance, and therefore has a wide application prospect in the technical field of PET label.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PET labels, in particular to a high-temperature resistant and waterproof PET label and a preparation process thereof. Background Art

[0002] PET labels, due to their unique material properties and versatility, have become a key material in modern packaging and labeling. PET is recyclable, aligning with the global trend toward green packaging. Compared to traditional PVC labels, PET does not release harmful substances during degradation, reducing the environmental impact. Furthermore, PET labels offer excellent weather resistance, tear resistance, and chemical stability, maintaining information integrity in high-temperature, humid, and oily environments, making them suitable for demanding applications such as food, pharmaceuticals, and cosmetics. Their high transparency (over 90%) and printability support diverse designs, enhancing brand visual appeal. However, in areas such as food and medical, where labels come into direct contact with products or the human body, bacteria and mold can easily grow, posing a risk of cross-contamination. Therefore, enhanced antimicrobial properties are needed to prevent bacterial and mold contamination of the contents. Furthermore, conventional labels are prone to blurring and peeling in humid, oily, or chemically corrosive environments. Enhanced waterproofing ensures long-term legibility in applications such as cold chain logistics and outdoor signage, reducing misuse and product rejection due to label damage.

[0003] In order to overcome the defects of the prior art, the present invention provides a high-temperature resistant and waterproof PET label and a preparation process thereof. Summary of the Invention

[0004] The object of the present invention is to provide a high-temperature resistant and waterproof PET label and a preparation process thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation process for a high-temperature-resistant and waterproof PET label comprises the following steps: applying an epoxy silicon coating to the surface of a PET film, allowing the coating to stand for 20-30 minutes, and then curing the film at 80-90°C for 7-10 minutes to obtain an antibacterial and waterproof PET film; applying an adhesive to one side of the antibacterial and waterproof PET film and laminating the film with a PET release paper; and coating the other side of the antibacterial and waterproof PET film with ink to obtain a finished product.

[0007] More optimally, the preparation process of the epoxy silicon coating is:

[0008] Step S1: adding chitosan to 1.8-2.0 wt% acetic acid, fully dispersing the mixture, and then dropwise adding 1.0-1.5 mg / mL sodium tripolyphosphate solution, stirring at 25-30° C. for 6-7 hours to obtain a chitosan solution; adding nano-titanium dioxide to ethanol, fully dispersing the mixture, and obtaining a titanium dioxide dispersion; slowly dropwise adding the titanium dioxide dispersion to the chitosan solution, stirring at 25-30° C. for 6-7 hours, and centrifuging and freeze-drying the mixture after the stirring is complete to obtain chitosan-coated titanium dioxide;

[0009] Step S2: adding chitosan-coated titanium dioxide to 1.8-2.0 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is complete, the mixture is washed and dried to obtain antibacterial modified chitosan microspheres;

[0010] Step S3: 0.25-0.30 mol / L methyltriethoxysilane solution, 0.15-0.20 mol / L diphenyldimethoxysilane solution and 0.07-0.09 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution are mixed, and the mixture is stirred for 25-35 minutes. Then, 37-40 wt% hydrochloric acid and deionized water are added, and the mixture is stirred and reacted at 80-85° C. for 6-7 hours. After the reaction is completed, the mixture is subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane and a curing agent are mixed to obtain an epoxidized silicon coating.

[0011] More optimally, in step S1, when preparing chitosan-coated titanium dioxide, the reaction mass ratio of chitosan to nano-titanium dioxide is (6-7):3.

[0012] More optimally, in step S2, the mass volume ratio of chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:(0.65-0.70) mL.

[0013] More optimally, in step S3, the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution is 8:8:(3-4), and the solvent used for the three solutions is ethanol; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and curing agent is (0.2-0.3) g:20 mL:(0.7-0.9) g:0.05 g; the curing agent is a polyamide curing agent.

[0014] More optimally, the preparation process of the adhesive is:

[0015] Step S1: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 10-12 hours. After stirring, centrifuging and freeze-drying to obtain antibacterial silica;

[0016] Step S2: Add antibacterial silica to anhydrous ethanol, fully disperse it, then add ammonia water and deionized water, stir and react for 40-50 minutes, then add hexadecyltrimethoxysilane, react at 60-70°C for 3-4 hours, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain hydrophobic silica; heat the epoxy resin until it is melted, then add hydrophobic silica, curing agent, dioctyl phthalate, and acetone, stir evenly, and obtain an adhesive.

[0017] More optimally, in step S1, the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol is 200 g: (8-9) mL: (4-5) mL.

[0018] More optimally, in step S2, the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is (6-7):1.

[0019] More optimally, in step S2, the contents of the adhesive components are: by mass, 15-17 parts of epoxy resin, 3-5 parts of hydrophobic silica, 7-8 parts of curing agent, 0.3-0.4 parts of dioctyl phthalate, and 3-5 parts of acetone; the curing agent is a polyamide curing agent.

[0020] Beneficial effects of the present invention:

[0021] The present invention is characterized by adding chitosan and nano-titanium dioxide to produce chitosan-coated titanium dioxide with antibacterial properties. Coating the titanium dioxide with chitosan improves the dispersibility of the nano-titanium dioxide, making it more evenly distributed throughout the system and increasing its contact area with bacteria and fungi, thereby enhancing the efficiency of photocatalytic sterilization. Furthermore, the antibacterial activity of chitosan synergizes with the photocatalytic antibacterial activity of titanium dioxide, achieving an antibacterial effect both under illuminated and dark conditions. The chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde are then mixed. Through emulsion polymerization, the chitosan-coated titanium dioxide molecules gradually crosslink with the antibacterial material, cinnamaldehyde, further enhancing the antibacterial properties and producing antibacterial modified chitosan microspheres. Furthermore, the antibacterial modified chitosan microspheres are mixed with isopropyl alcohol, epoxidized methylphenyl polysiloxane, and a curing agent to produce an epoxidized silicon coating. The epoxidized silicon coating is then applied to the surface of a PET film, allowed to stand, and cured to produce an antibacterial and waterproof PET film. The epoxidized methylphenyl polysiloxane can be fully cured and cross-linked with the remaining amino groups in the antibacterial modified chitosan microspheres, and the polyamide curing agent can be fully cured and cross-linked at 80-90°C, ultimately obtaining an antibacterial and waterproof PET film with excellent antibacterial and waterproof properties.

[0022] The present invention is characterized in that, by adding mesoporous nano-silica, eugenol and carvacrol, eugenol and carvacrol with antibacterial properties are loaded into mesoporous nano-silica to obtain antibacterial silica. Furthermore, hexadecyltrimethoxysilane is used to modify the antibacterial silica to obtain hydrophobic silica with a long hydrophobic chain. Epoxy resin is heated to melting, and then hydrophobic silica, a curing agent, dioctyl phthalate and acetone are added and stirred to obtain an adhesive. One side of the antibacterial and waterproof PET film is coated with adhesive and compounded with a PET release paper, and the other side of the antibacterial and waterproof PET film is coated with ink to obtain a finished product. Since the epoxy silicon coating and the epoxy resin adhesive are both epoxy systems, the interfacial compatibility is high, and the interlayer peeling caused by the polarity difference can be effectively avoided, so the antibacterial and waterproof PET film and the epoxy resin adhesive have a good bonding effect.

[0023] In summary, the epoxy silicon coating contains antimicrobial modified chitosan microspheres, which are applied to the surface of the PET film to form an antimicrobial and waterproof PET film. This film not only prevents the intrusion of external bacteria but also kills bacteria it comes into contact with, thus serving a dual purpose of protection and antimicrobial protection. Furthermore, the adhesive incorporates modified hydrophobic silica, whose antimicrobial properties further enhance the antimicrobial properties of the PET label. Furthermore, the hydrophobic properties of the hydrophobic silica prevent moisture intrusion, preventing bacterial growth caused by moisture. Together with the antimicrobial and waterproof PET film, it creates an overall antimicrobial and waterproof structure. Furthermore, the hydrophobic methyl / phenyl structure of the epoxy silicon coating and the hydrophobic silica in the adhesive create a double barrier, blocking water penetration and ensuring that the PET label maintains adhesive stability even in humid environments. DETAILED DESCRIPTION

[0024] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0025] Source of raw materials:

[0026] Chitosan, provided by Jiangsu Caiwei Biotechnology Co., Ltd., with a particle size of 80 mesh; nano-titanium dioxide, provided by Nanjing Baoket New Materials Co., Ltd., with a particle size of 30nm; liquid paraffin, provided by Hebei Wantai Chemical Co., Ltd., model 15#; polyamide curing agent is specifically 651 type polyamide curing agent; acrylic adhesive, provided by Shandong Xingshun Chemical Co., Ltd., with a density of 0.955kg / m3, and the model is national standard; mesoporous nano-silica is provided by Dalian Zeer Catalytic Materials Co., Ltd., with a pore size of 3nm; epoxy resin, provided by Jinan Qingtian Chemical Technology Co., Ltd., model E44; in terms of mass, one part is 1g.

[0027] Example 1: Step S1: chitosan is added to 2.0 wt% acetic acid, and after being fully dispersed, a 1.5 mg / mL sodium tripolyphosphate solution is added dropwise, and the mixture is stirred at 30°C for 7 hours to obtain a chitosan solution; nano-titanium dioxide is added to ethanol and fully dispersed to obtain a titanium dioxide dispersion; the titanium dioxide dispersion is slowly added dropwise to the chitosan solution, and stirred at 30°C for 7 hours. After the stirring is completed, the mixture is centrifuged and freeze-dried to obtain chitosan-coated titanium dioxide; when preparing the chitosan-coated titanium dioxide, the reaction mass ratio of chitosan to nano-titanium dioxide is 6.5:3;

[0028] Step S2: adding chitosan-coated titanium dioxide to 2.0 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is completed, washing and drying are performed to obtain antibacterial modified chitosan microspheres; the mass volume ratio of the chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:0.67 mL;

[0029] Step S3: 0.30 mol / L methyltriethoxysilane solution, 0.20 mol / L diphenyldimethoxysilane solution and 0.09 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution were mixed and stirred for 35 min, and then 40 wt% hydrochloric acid and deionized water were added, and the mixture was stirred at 85 ° C for 7 h. After the reaction was completed, the mixture was subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; the antibacterial modified chitosan microspheres were prepared. , isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent are mixed to obtain epoxidized silicon coating; the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution is 8:8:3.5; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent is 0.25g:20mL:0.8g:0.05g;

[0030] Step S4: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 12 hours. After stirring, centrifuging and freeze-drying to obtain antibacterial silica; the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol is 200 g:8.5 mL:4.5 mL;

[0031] Step S5: adding the antibacterial silica to anhydrous ethanol, adding ammonia water and deionized water after fully dispersing, stirring and reacting for 50 minutes, then adding hexadecyltrimethoxysilane, reacting at 70°C for 4 hours, centrifuging, washing, and vacuum drying after the reaction to obtain hydrophobic silica; heating 17g of epoxy resin until melted, adding 5g of hydrophobic silica, 8g of polyamide curing agent, 0.4g of dioctyl phthalate, and 5g of acetone, stirring evenly to obtain an adhesive; the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is 6.5:1;

[0032] Step S6: Apply the epoxy silicon coating to the surface of the PET film, let it stand for 30 minutes, and then cure it at 90°C for 10 minutes to obtain an antibacterial and waterproof PET film; then apply adhesive to one side of the antibacterial and waterproof PET film and compound it with a PET release paper, and apply ink to the other side of the antibacterial and waterproof PET film to obtain a finished product.

[0033] Example 2: Step S1: chitosan was added to 1.9 wt % acetic acid, and after being fully dispersed, a 1.2 mg / mL sodium tripolyphosphate solution was added dropwise, and the mixture was stirred at 27° C. for 6.5 h to obtain a chitosan solution; nano-titanium dioxide was added to ethanol, and after being fully dispersed, a titanium dioxide dispersion was obtained; the titanium dioxide dispersion was slowly added dropwise to the chitosan solution, and stirred at 27° C. for 6.5 h. After the stirring was completed, the mixture was centrifuged and freeze-dried to obtain chitosan-coated titanium dioxide; when preparing chitosan-coated titanium dioxide, the reaction mass ratio of chitosan to nano-titanium dioxide was 6.5:3;

[0034] Step S2: adding chitosan-coated titanium dioxide to 1.9 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is completed, the mixture is washed and dried to obtain antibacterial modified chitosan microspheres; the mass volume ratio of the chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:0.67 mL;

[0035] Step S3: 0.27 mol / L methyltriethoxysilane solution, 0.17 mol / L diphenyldimethoxysilane solution and 0.08 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution were mixed and stirred for 30 min, and then 39 wt% hydrochloric acid and deionized water were added, and the mixture was stirred at 82 ° C for 6.5 h. After the reaction was completed, the mixture was subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; the antibacterial modified chitosan microporous Chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent were mixed to obtain epoxidized silicon coating; the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution was 8:8:3.5; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent was 0.25 g:20 mL:0.8 g:0.05 g;

[0036] Step S4: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 11 hours. After stirring, centrifuging and freeze-drying to obtain antibacterial silica; the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol is 200 g:8.5 mL:4.5 mL;

[0037] Step S5: adding the antibacterial silica to anhydrous ethanol, adding ammonia water and deionized water after fully dispersing, stirring and reacting for 45 minutes, then adding hexadecyltrimethoxysilane, reacting at 65°C for 3.5 hours, centrifuging, washing, and vacuum drying after the reaction to obtain hydrophobic silica; heating 17g of epoxy resin until melted, adding 5g of hydrophobic silica, 8g of polyamide curing agent, 0.4g of dioctyl phthalate, and 5g of acetone, stirring evenly to obtain an adhesive; the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is 6.5:1;

[0038] Step S6: Apply the epoxy silicon coating to the surface of the PET film, let it stand for 25 minutes, and then cure it at 85°C for 9 minutes to obtain an antibacterial and waterproof PET film; then apply adhesive to one side of the antibacterial and waterproof PET film and compound it with a PET release paper, and apply ink to the other side of the antibacterial and waterproof PET film to obtain a finished product.

[0039] Example 3: Step S1: chitosan was added to 1.8 wt % acetic acid, and after being fully dispersed, a 1 mg / mL sodium tripolyphosphate solution was added dropwise, and the mixture was stirred at 25° C. for 6 h to obtain a chitosan solution; nano-titanium dioxide was added to ethanol, and after being fully dispersed, a titanium dioxide dispersion was obtained; the titanium dioxide dispersion was slowly added dropwise to the chitosan solution, and stirred at 25° C. for 6 h. After the stirring was completed, the mixture was centrifuged and freeze-dried to obtain chitosan-coated titanium dioxide; when preparing the chitosan-coated titanium dioxide, the reaction mass ratio of chitosan to nano-titanium dioxide was 6.5:3;

[0040] Step S2: adding chitosan-coated titanium dioxide to 1.8 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is completed, washing and drying are performed to obtain antibacterial modified chitosan microspheres; the mass volume ratio of the chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:0.67 mL;

[0041] Step S3: 0.25 mol / L methyltriethoxysilane solution, 0.15 mol / L diphenyldimethoxysilane solution and 0.07 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution were mixed and stirred for 25 min, and then 37 wt% hydrochloric acid and deionized water were added and stirred at 80 ° C for 6 h. After the reaction was completed, the mixture was subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; the antibacterial modified chitosan microspheres were prepared. , isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent are mixed to obtain epoxidized silicon coating; the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution is 8:8:3.5; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent is 0.25g:20mL:0.8g:0.05g;

[0042] Step S4: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 10 hours. After stirring, centrifuging and freeze-drying to obtain antibacterial silica; the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol is 200 g:8.5 mL:4.5 mL;

[0043] Step S5: adding the antibacterial silica to anhydrous ethanol, fully dispersing, adding ammonia water and deionized water, stirring and reacting for 40 minutes, then adding hexadecyltrimethoxysilane, reacting at 60°C for 3 hours, centrifuging, washing, and vacuum drying after the reaction to obtain hydrophobic silica; heating 17g of epoxy resin until melted, adding 5g of hydrophobic silica, 8g of polyamide curing agent, 0.4g of dioctyl phthalate, and 5g of acetone, stirring evenly to obtain an adhesive; the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is 6.5:1;

[0044] Step S6: Apply the epoxy silicon coating to the surface of the PET film, let it stand for 20 minutes, and then cure it at 80°C for 7 minutes to obtain an antibacterial and waterproof PET film; then apply adhesive to one side of the antibacterial and waterproof PET film and compound it with a PET release paper, and apply ink to the other side of the antibacterial and waterproof PET film to obtain a finished product.

[0045] Comparative Example 1: The epoxy silicon coating was removed, and the rest was the same as in Example 1, with the following specific steps: Step S1: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 12 hours. After stirring, centrifugation and freeze-drying were performed to obtain antibacterial silica; the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol was 200 g:8.5 mL:4.5 mL;

[0046] Step S2: adding antibacterial silica to anhydrous ethanol, adding ammonia water and deionized water after fully dispersing, stirring and reacting for 50 minutes, then adding hexadecyltrimethoxysilane, reacting at 70°C for 4 hours, centrifuging, washing, and vacuum drying after the reaction to obtain hydrophobic silica; heating 17g of epoxy resin until melted, adding 5g of hydrophobic silica, 8g of polyamide curing agent, 0.4g of dioctyl phthalate, and 5g of acetone, stirring evenly to obtain an adhesive; the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is 6.5:1;

[0047] Step S3: coating one side of the PET film with adhesive and laminating it with a PET release paper, and coating the other side of the PET film with ink to obtain a finished product.

[0048] Comparative Example 2: The adhesive was replaced with an acrylic adhesive provided by Shandong Xingshun Chemical Co., Ltd., and the rest was the same as Example 1, and the specific steps were as follows: Step S1: chitosan was added to 2.0 wt% acetic acid, and after being fully dispersed, 1.5 mg / mL sodium tripolyphosphate solution was added dropwise, and stirred at 30°C for 7 hours to obtain a chitosan solution; nano-titanium dioxide was added to ethanol and fully dispersed to obtain a titanium dioxide dispersion; the titanium dioxide dispersion was slowly added dropwise to the chitosan solution, stirred at 30°C for 7 hours, and after the stirring was completed, centrifuged and freeze-dried to obtain chitosan-coated titanium dioxide; when preparing chitosan-coated titanium dioxide, the reaction mass ratio of chitosan and nano-titanium dioxide was 6.5:3;

[0049] Step S2: adding chitosan-coated titanium dioxide to 2.0 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is completed, washing and drying are performed to obtain antibacterial modified chitosan microspheres; the mass volume ratio of the chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:0.67 mL;

[0050] Step S3: 0.30 mol / L methyltriethoxysilane solution, 0.20 mol / L diphenyldimethoxysilane solution and 0.09 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution were mixed and stirred for 35 min, and then 40 wt% hydrochloric acid and deionized water were added, and the mixture was stirred at 85 ° C for 7 h. After the reaction was completed, the mixture was subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; the antibacterial modified chitosan microspheres were prepared. , isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent are mixed to obtain epoxidized silicon coating; the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution is 8:8:3.5; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and polyamide curing agent is 0.25g:20mL:0.8g:0.05g;

[0051] Step S4: Apply the epoxy silicon coating to the surface of the PET film, let it stand for 30 minutes, and then cure it at 90°C for 10 minutes to obtain an antibacterial and waterproof PET film; then coat one side of the antibacterial and waterproof PET film with acrylic adhesive and compound it with a PET release paper, and coat the other side of the antibacterial and waterproof PET film with ink to obtain a finished product.

[0052] Detection test:

[0053] Antibacterial Performance Testing: The finished product prepared in this invention was used as a sample, with a sample size of 30×30 mm. Escherichia coli was cultured as the test strain and diluted to obtain a bacterial solution. The sample was placed in a petri dish containing the bacterial solution and incubated at 25°C for one day. After the incubation period, the colonies in the sample group were counted. A control group was also cultured and the colonies in the control group were counted after the incubation period. The data were then used to calculate the antibacterial rate.

[0054] Water contact angle test: The finished product prepared by the present invention was used as a sample with a sample size of 30×30 mm. The surface contact angle test was performed on the sample surface using a surface contact angle tester produced by Dataphysics Company of Germany.

[0055] Water Vapor Transmission Rate Test: Referring to GB / T 21529-2008, "Plastic Film and Sheeting - Determination of Water Vapor Transmission Rate - Electrolytic Sensor Method," the finished product prepared in this invention was used as a sample. The sample size was 30 × 30 mm. The water vapor transmission rate of the sample was tested using a water vapor transmission rate tester at a temperature of 30°C and a relative humidity of 95%. The results are shown in the following table:

[0056]

[0057] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. It can be seen from the experimental data that there is no obvious fluctuation in the various properties of the sample. Comparative Example 1: The epoxy silicon coating is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate is reduced to 75.3%, the water contact angle is reduced to 136°, and the water vapor permeability is increased to 0.097g / (m·h). The reasons are analyzed as follows: the hydrophobic methyl / phenyl structure in the epoxy silicon coating has good waterproof properties; in addition, the antibacterial modified chitosan microspheres in the epoxy silicon coating contain a variety of antibacterial components chitosan, titanium dioxide, and cinnamaldehyde, so it has excellent antibacterial properties; so after removing the epoxy silicon coating, the antibacterial rate is reduced, the water contact angle is reduced, and the water vapor permeability is increased.

[0058] Comparative Example 2: The adhesive was replaced with an acrylic adhesive provided by Shandong Xingshun Chemical Co., Ltd., and the rest was the same as in Example 1. The experimental data showed that compared with Example 1, the antibacterial rate was reduced to 88.5%, the water contact angle was reduced to 78°, and the water vapor permeability was increased to 0.129 g / (m·h). The reasons for this were as follows: the adhesive prepared by the present invention contains hydrophobic silica, so it has good waterproof properties; in addition, the adhesive also contains eugenol and carvacrol antibacterial ingredients, so after removing them, the antibacterial rate is reduced, the water contact angle is reduced, and the water vapor permeability is increased.

[0059] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include," "comprise," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0060] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A process for preparing a high-temperature resistant and waterproof PET label, characterized by: The following steps are involved: The epoxy silicon coating is applied to the surface of the PET film, and the film is allowed to stand for 20-30 minutes and then cured at 80-90° C. for 7-10 minutes to obtain an antibacterial and waterproof PET film; an adhesive is then applied to one side of the antibacterial and waterproof PET film and the film is laminated with a PET release paper; and the other side of the antibacterial and waterproof PET film is coated with ink to obtain a finished product; Among them, the preparation process of epoxy silicon coating is: Step S1: adding chitosan to 1.8-2.0 wt% acetic acid, fully dispersing the mixture, and then dropwise adding 1.0-1.5 mg / mL sodium tripolyphosphate solution, stirring at 25-30° C. for 6-7 hours to obtain a chitosan solution; adding nano-titanium dioxide to ethanol, fully dispersing the mixture, and obtaining a titanium dioxide dispersion; slowly dropwise adding the titanium dioxide dispersion to the chitosan solution, stirring at 25-30° C. for 6-7 hours, and centrifuging and freeze-drying the mixture after the stirring is complete to obtain chitosan-coated titanium dioxide; Step S2: adding chitosan-coated titanium dioxide to 1.8-2.0 wt% acetic acid and fully dispersing the mixture to obtain a dispersion; then adding Span 80 to liquid paraffin and stirring the mixture to obtain a surfactant solution; dropwise adding the dispersion to the surfactant solution, and then adding cinnamaldehyde to carry out a cross-linking reaction. After the reaction is completed, the mixture is washed and dried to obtain antibacterial modified chitosan microspheres; Step S3: 0.25-0.30 mol / L methyltriethoxysilane solution, 0.15-0.20 mol / L diphenyldimethoxysilane solution and 0.07-0.09 mol / L γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution are mixed, and the mixture is stirred for 25-35 minutes. Then, 37-40 wt% hydrochloric acid and deionized water are added, and the mixture is stirred and reacted at 80-85° C. for 6-7 hours. After the reaction is completed, the mixture is subjected to rotary evaporation and separation to obtain epoxidized methylphenyl polysiloxane; antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane and a curing agent are mixed to obtain an epoxidized silicon coating.

2. The process for preparing a high-temperature resistant and waterproof PET label according to claim 1, wherein: In step S1, when preparing chitosan-coated titanium dioxide, the reaction mass ratio of chitosan to nano-titanium dioxide is [6-7]:

3.

3. The process for preparing a high temperature resistant and waterproof PET label according to claim 1, wherein: In step S2, the mass volume ratio of chitosan-coated titanium dioxide, Span 80, and cinnamaldehyde is 2 g:4 mL:[0.65-0.70] mL.

4. The process for preparing a high-temperature resistant and waterproof PET label according to claim 1, wherein: In step S3, the reaction mass ratio of methyltriethoxysilane solution, diphenyldimethoxysilane solution, and γ-(2,3-cyclopropyloxy)propyltrimethoxysilane solution is 8:8:[3-4], and the solvent used in the three solutions is ethanol; the mixed mass volume ratio of antibacterial modified chitosan microspheres, isopropyl alcohol, epoxidized methylphenyl polysiloxane, and curing agent is [0.2-0.3] g:20 mL:[0.7-0.9] g:0.05 g; the curing agent is a polyamide curing agent.

5. The process for preparing a high temperature resistant and waterproof PET label according to claim 1, wherein: The preparation process of the adhesive is: Step S1: adding mesoporous nano-silica to anhydrous ethanol, fully dispersing, then adding eugenol and carvacrol, and magnetically stirring for 10-12 hours. After stirring, centrifuging and freeze-drying to obtain antibacterial silica; Step S2: Add antibacterial silica to anhydrous ethanol, fully disperse it, then add ammonia water and deionized water, stir and react for 40-50 minutes, then add hexadecyltrimethoxysilane, react at 60-70°C for 3-4 hours, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain hydrophobic silica; heat the epoxy resin until it is melted, then add hydrophobic silica, curing agent, dioctyl phthalate, and acetone, stir evenly, and obtain an adhesive.

6. The process for preparing a high-temperature resistant and waterproof PET label according to claim 5, wherein: In step S1, the reaction mass volume ratio of mesoporous nano-silica, eugenol, and carvacrol is 200 g: [8-9] mL: [4-5] mL.

7. The process for preparing a high-temperature resistant and waterproof PET label according to claim 5, wherein: In step S2, the reaction mass ratio of antibacterial silica to hexadecyltrimethoxysilane is [6-7]:

1.

8. The process for preparing a high-temperature resistant and waterproof PET label according to claim 5, wherein: In step S2, the contents of the adhesive components are as follows: by mass: 15-17 parts of epoxy resin, 3-5 parts of hydrophobic silica, 7-8 parts of curing agent, 0.3-0.4 parts of dioctyl phthalate, and 3-5 parts of acetone; the curing agent is a polyamide curing agent.

9. A high temperature resistant and waterproof PET label, characterized in that: Prepared according to the preparation process according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-strength washable protective film as well as preparation method and application thereof

    CN118006233A

  • High-temperature-resistant waterproof PET label and preparation process thereof

    CN118652633A